2020
DOI: 10.3390/cancers12113218
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein, Protein Induced by Vitamin K Absence or Antagonist II and Glypican-3 for the Detection and Prediction of Hepatocellular Carcinoma in Patients with Cirrhosis of Viral Etiology

Abstract: International guidelines recommend the use of ultrasound as a surveillance tool for hepatocellular carcinoma (HCC) in patients with cirrhosis, while the role of serum biomarkers is still debated. We investigated serum alpha-fetoprotein (AFP), protein induced by vitamin K absence or antagonist II (PIVKA-II) and glypican-3 (GPC-3) diagnostic accuracy for HCC detection and prediction in patients with liver cirrhosis of viral etiology under surveillance. A total of 349 patients (200 cirrhosis and 149 HCC) were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Many recent studies evaluated individual and combined diagnostic values of serum alpha-fetoprotein (AFP), des-gamma-carboxyprothrombin (DCP), glypican-3 (GPC3) and golgi protein 73 (GP73) in diagnosing HCC. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] One study by Li et al showed combination of serum levels of miR-122, GPC3 and AFP improved power of HCC detection. 66 Several studies showed that the sensitivity of circulating GPC3 is superior to AFP for detecting HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies evaluated individual and combined diagnostic values of serum alpha-fetoprotein (AFP), des-gamma-carboxyprothrombin (DCP), glypican-3 (GPC3) and golgi protein 73 (GP73) in diagnosing HCC. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] One study by Li et al showed combination of serum levels of miR-122, GPC3 and AFP improved power of HCC detection. 66 Several studies showed that the sensitivity of circulating GPC3 is superior to AFP for detecting HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies performed in patients with NAFLD [ 39 , 40 ], we observed a good diagnostic accuracy for PIVKA-II (AUC = 0.853) and a moderate performance for AFP (AUC = 0.763). Interestingly, GPC-3 showed a higher accuracy compared to the results of our previous study carried out on a cohort of patients with viral related-HCC [ 18 ]. Possibly, both the diverse etiology and clinical characteristics of the patients included may have accounted for the discrepancy observed.…”
Section: Discussionmentioning
confidence: 73%
“…Among the traditional HCC biomarkers, protein induced by vitamin K absence or antagonist II (PIVKA-II), alone or in combination with alpha-fetoprotein (AFP), showed promising results for the early detection, and even for the prediction, of HCC in patients with cirrhosis of viral etiology [ 17 , 18 , 19 , 20 ]. However, the data on NAFLD-related HCC are scant.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, hypoxia altering the actin molecules making up their cytoskeleton impairs the endocytosis of vitamin K, and the subsequent vitamin K deficiency leads to the release into the circulation of vitamin K deficient prothrombin without complete carboxylation [ 23 ]. On the other hand, PIVKA-II appears to be also involved in neo-angiogenesis [ 24 ] and able to act as a mitogen stimulating the growth of HCC cells [ 25 ], thus contributing to the increased risk of HCC in cirrhotic patients [ 26 , 27 ]. Altogether, these data support the interpretation that PIVKA-II production by cancer cells is increased by ischemia and tend to stimulate angiogenesis.…”
Section: Discussionmentioning
confidence: 99%